2013
DOI: 10.1002/ece3.783
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila rely on learning while foraging under semi‐natural conditions

Abstract: Learning is predicted to affect manifold ecological and evolutionary processes, but the extent to which animals rely on learning in nature remains poorly known, especially for short-lived non-social invertebrates. This is in particular the case for Drosophila, a favourite laboratory system to study molecular mechanisms of learning. Here we tested whether Drosophila melanogaster use learned information to choose food while free-flying in a large greenhouse emulating the natural environment. In a series of exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 60 publications
(110 reference statements)
0
10
0
Order By: Relevance
“…Associative learning occurs when herbivores associate specific cues of a host plant (e.g., color, odors, taste, or shape) with a positive reward, such as successful oviposition or acquiring suitable food resources (Jones & Agrawal, 2017). The cues associated with the positive reward will be the most receptive in later foraging and thus allow the herbivore to more rapidly locate its host (Cunningham et al, 1998(Cunningham et al, , 2004(Cunningham et al, , 2006Cunningham et al, 1999;Mery & Kawecki, 2002;Riffell et al, 2008;Simões et al, 2011;Zrelec et al, 2013). As examples, desert locusts, Schistocerca gregaria, are able to associate plant odors with food rewards and this improved subsequent attraction to such odors following learning trials (Simões et al, 2011).…”
Section: Using Previous Experience To Optimize Host Foragingmentioning
confidence: 99%
“…Associative learning occurs when herbivores associate specific cues of a host plant (e.g., color, odors, taste, or shape) with a positive reward, such as successful oviposition or acquiring suitable food resources (Jones & Agrawal, 2017). The cues associated with the positive reward will be the most receptive in later foraging and thus allow the herbivore to more rapidly locate its host (Cunningham et al, 1998(Cunningham et al, , 2004(Cunningham et al, , 2006Cunningham et al, 1999;Mery & Kawecki, 2002;Riffell et al, 2008;Simões et al, 2011;Zrelec et al, 2013). As examples, desert locusts, Schistocerca gregaria, are able to associate plant odors with food rewards and this improved subsequent attraction to such odors following learning trials (Simões et al, 2011).…”
Section: Using Previous Experience To Optimize Host Foragingmentioning
confidence: 99%
“…Being able to develop acceptance or even develop a preference to a novel food source is certainly adaptive in the face of starvation. It is, thus, not surprising that many animals seem to have evolved innate mechanisms that translate early experiences with food into later preferences for that same food (Doherty and Cowie 1994;Punzo 2002;Scherer et al 2003;Punzo 2004;Darmaillacq et al 2006;Schausberger et al 2010;Zrelec et al 2013;Arenas and Farina 2014;McAulay et al 2015;Crane et al 2018). Furthermore, transmitting these learned food preferences to the next generation would also be adaptive as the novel food source is likely to continue to be present in the environment of the offspring.…”
mentioning
confidence: 99%
“…The innate preference of inexperienced parasitoids for hostplus non-host caterpillar-damaged plants could be caused by a quantitative difference in emitted volatiles related to caterpillar feeding, as a result of unequal numbers of caterpillars on the two plant infestation types (Geervliet et al, 1998a). Only very few previous studies have shown that insects that can learn to associate cues with the presence of their host/food in the laboratory also accordingly show altered behaviour in (semi-)field situations (Lewis & Martin, 1990;Hare et al, 1997;Raine & Chittka, 2008;Zrelec et al, 2013;Janssen et al, 2014;Kruidhof et al, 2015). Quantitative differences could also have occurred because of changed emission rates of caterpillar-related volatile compounds due to co-infestation by phloem-feeding insects such as aphids (Rodriguez-Saona et al, 2003;Zhang et al, 2013;Ponzio et al, 2016;Li et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This new experience levelled out the preference for plants induced by only host caterpillars in the wind-tunnel experiment. Only very few previous studies have shown that insects that can learn to associate cues with the presence of their host/food in the laboratory also accordingly show altered behaviour in (semi-)field situations (Lewis & Martin, 1990;Hare et al, 1997;Raine & Chittka, 2008;Zrelec et al, 2013;Janssen et al, 2014;Kruidhof et al, 2015). Cotesia glomerata is well known for its ability to learn in the laboratory (Geervliet et al, 1998a,b;Bleeker et al, 2006;Smid et al, 2007;Kruidhof et al, 2012a,b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation